Influence of Romance and Germanic Languages on the Morphology of the Days of the Week in Papiamentu - Liska, Geraldo Jose Rodrigues (Revista Letra Magna, 2024)
In this work, we investigated how the names of the days of the week were formed in a philological and lexical approach in the Romance and Germanic languages and how they influenced the formation of Papiamento, based on philological research already carried out and consultation to various dictionaries and translation tools. We observed that, in semantic issues, Papiamentu had the formation of the names of its days of the week from Portuguese and Spanish influences; on the other hand, in morphosyntactic constructions, the Germanic structure prevails, especially Dutch. This is interesting when we keep in mind that, the more we understand about human cognition, the more we realize the importance of linguistic processes, both for the way man sees, thinks and represents the world, and for the definition of his own humanity.